Plantacyanin Plays a Role in Reproduction in Arabidopsis - Dong, Juan (American Society of Plant Biologists, 2005)
Plantacyanins belong to the phytocyanin family of blue copper proteins. In the Arabidopsis (Arabidopsis thaliana) genome, only one gene encodes plantacyanin. The T-DNA-tagged mutant is a knockdown mutant that shows no visible phenotype. We used both promoter-β-glucuronidase transgenic plants and immunolocalization to show that Arabidopsis plantacyanin is expressed most highly in the inflorescence and, specifically, in the transmitting tract of the pistil. Protein levels show a steep gradient in expression from the stigma into the style and ovary. Overexpression plants were generated using cauliflower mosaic virus 35S, and protein levels in the pistil were examined as well as the pollination process. Seed set in these plants is highly reduced mainly due to a lack of anther dehiscence, which is caused by degeneration of the endothecium. Callose deposits occur on the pollen walls in plants that overexpress plantacyanin, and a small percentage of these pollen grains germinate in the closed anthers. When wild-type pollen was used on the overexpression stigma, seed set was still decreased compared to the control pollinations. We detected an increase in plantacyanin levels in the overexpression pistil, including the transmitting tract. Guidance of the wild-type pollen tube on the overexpression stigma is disrupted as evidenced by the growth behavior of pollen tubes after they penetrate the papillar cell. Normally, pollen tubes travel down the papilla cell and into the style. Wild-type pollen tubes on the overexpression stigma made numerous turns around the papilla cell before growing toward the style. In some rare cases, pollen tubes circled up the papilla cell away from the style and were arrested there. We propose that when plantacyanin levels in the stigma are increased, pollen tube guidance into the style is disrupted.